YHWH and the God of philosophical theology - Gericke, Jaco (Verbum et ecclesia, 2005)
In popular orthodox Christian philosophical theology, it is often taken for granted that the divine philosophised about is none other than the Hebrew deity YHWH himself. Moreover , it is often assumed that the Old Testament depicts YHWH as being, inter alia, single, omnipotent, omniscient, omnipresent, and eternal. Now while it is to be admitted that there are indeed depictions of YHWH in the Old Testament in which his profile might be thought of as corresponding more or less to the popular philosophical ideal, it is also true that there are many representations that contradict it. In this article, the author looks at how the popular profile of YHWH in the Old Testament as reconstructed by some philosophical theologians claiming to be ‘biblical’ is deconstructed when it is juxtaposed with alternative renderings of the divine in the same texts.